Winter Embolism and Recovery in the Conifer Shrub Pinus mugo L. - Stefan Mayr (Forests, 2019)
Research Highlights: Pronounced winter embolism and recovery were observed in the Alpine conifer shrub Pinus mugo L. Data indicated that the hydraulic courses and underlying mechanism were similar to timberline trees. Background and Objectives: At high elevation, plants above the snow cover are exposed to frost drought and temperature stress during winter. Previous studies demonstrated winter stress to induce low water potentials (Ψ) and significant xylem embolism (loss of conductivity, or LC) in evergreen conifer trees, and recovery from embolism in late winter. Here, we analyzed xylem hydraulics and related structural and cellular changes in a conifer shrub species. Materials and Methods: The uppermost branches of Pinus mugo shrubs growing at the Alpine timberline were harvested over one year, and the Ψ, water content, LC, proportion of aspirated pits, and carbohydrate contents were analyzed. Results: Minimum Ψ (−1.82 ± 0.04 MPa) and maximum LC (39.9% ± 14.5%) values were observed in mid and late winter, followed by a recovery phase. The proportion of aspirated pits was also highest in winter (64.7% ± 6.9% in earlywood, 27.0% ± 1.4% in latewood), and decreased in parallel with hydraulic recovery in late winter and spring. Glucose and fructose contents gradually decreased over the year, while starch contents (also microscopically visible as starch grains in needle and stem tissues) increased from May to July. Conclusions: The formation and recovery of embolism in Pinus mugo were similar to those of timberline trees, as were the underlying mechanisms, with pit aspiration enabling the isolation of embolized tracheids, and changes in carbohydrate contents indicating adjustments of osmotic driving forces for water re-distribution. The effects of future changes in snow cover regimes may have pronounced and complex effects on shrub-like growth forms, because a reduced snow cover may shorten the duration of frost drought, but expose the plants to increased temperature stress and impair recovery processes.